2018
DOI: 10.3390/nano8050342
|View full text |Cite
|
Sign up to set email alerts
|

Doped Carbon Dots for Sensing and Bioimaging Applications: A Minireview

Abstract: In the last decade, carbon dots (C-dots, CDs) or carbon quantum dots (CQDs) have attracted a considerable amount of attention from the scientific community as a low cost and biocompatible alternative to semiconductor quantum dots. In particular, doped C-dots have excellent fluorescent properties that have been successfully utilized for numerous applications. In this minireview, we overview the recent advances on the synthesis of doped C-dots derived from carbon-rich sources and their potential applications for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
106
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(114 citation statements)
references
References 69 publications
1
106
0
Order By: Relevance
“…Carbon dots (CDs) is a relatively new carbon nanomaterial that has been extensively studied the last decade, due to its unique characteristics and properties. Strong photoluminescence, easy and low-cost preparative methods, stability, biocompatibility, and low toxicity are the main characteristics and properties of CDs that have attracted a huge interest for their use in various potential applications, especially in bio sensing and imaging, as well as in light emitting devices, fluorescence probes, environmental engineering, and photocatalysis [1][2][3][4][5][6][7]. Among a plethora of different procedures that have been presented up to now, microwave or thermal pyrolysis, electrochemical oxidation, hydrothermal treatments, and laser ablation are the most common approaches to create CDs.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon dots (CDs) is a relatively new carbon nanomaterial that has been extensively studied the last decade, due to its unique characteristics and properties. Strong photoluminescence, easy and low-cost preparative methods, stability, biocompatibility, and low toxicity are the main characteristics and properties of CDs that have attracted a huge interest for their use in various potential applications, especially in bio sensing and imaging, as well as in light emitting devices, fluorescence probes, environmental engineering, and photocatalysis [1][2][3][4][5][6][7]. Among a plethora of different procedures that have been presented up to now, microwave or thermal pyrolysis, electrochemical oxidation, hydrothermal treatments, and laser ablation are the most common approaches to create CDs.…”
Section: Introductionmentioning
confidence: 99%
“…de Sousa et al, assessed antimicrobial and anti-adherent potential of xylitol against two Pseudomonas aeruginosa strains (ATCC 9027 and clinical) and found that xylitol didn't have any bactericidal activity against these strains, however it suppress microbial growth by inhibit the bacterial adherence [24]. Similar results were also warranted by Radmerikhi et al, while evaluating the effect of xylitol on Streptococcus mutans and Lactobacillus acidophilus growth [19].…”
Section: Discussionmentioning
confidence: 76%
“…Applications of xylitol is wide spread however, size reduction of any product specifically food and drug results in improved efficacy. Fluorescent carbon dots (FCDs), synthesized from natural carbon sources are gaining huge attention as new class of nanomaterials are superior to traditional and conventional nano materials due to their solubility in water, bio-compatibility non-toxicity, applications in bio-imaging, drug delivery, cancer therapy and gene delivery[23][24]. Therefore carbon dots (8.87 nm) of purified xylitol were prepared and evaluated along with conventional antimicrobial compounds against selected human pathogens.…”
mentioning
confidence: 99%
“…Carbon dots (CDots) [1,2] which are generally defined as small carbon nanoparticles with various surface passivation schemes ( Figure 1) [3] have attracted much attention, as reflected by the large and ever increasing number of relevant publications in the literature [4][5][6][7][8][9][10][11][12][13][14][15]. On the preparation of CDots, the originally reported dot samples were synthesized by chemically functionalizing pre-processed and selected small carbon nanoparticles [1,2], thus structurally adhering more closely or literally to the definition (Figure 1).…”
Section: Introductionmentioning
confidence: 99%